2011
DOI: 10.5539/ibr.v4n4p153
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Stress in Multinational Companies in Thailand

Abstract: Both quantitative and qualitative data were collected for this research. A total of 513 questionnaires were returned. Structural Equation Modeling techniques were used for statistical data analysis. The results of the analysis were used as a guideline to interview six managers. This research reveals: first, positive stress is the key factor for enhance job satisfaction based on the principle that stress should be moderately stimulated while excessive stimulation is likely to cause physical, and mental illnesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In a Japanese workplace, for example, where there is unfailing preference for collective responsibility, it is the obligation of higher-level managers to accept symbolic responsibility for the failures of their groups or group members (Morioka Todeschini, 2011). Further, although teamwork is the norm in workplaces from societies with traditionally high levels of collectivism (Jarinto, 2011), collective responsibility is not associated with all collectivistic cultures equally (Morioka Todeschini, 2011). Rather, different degrees of collective responsibility preference prevalent in different cultures may be associated more closely with the GLOBE study's (House et al, 2004) cultural value of institutional collectivism.…”
Section: Collective Responsibility Preferencementioning
confidence: 99%
See 2 more Smart Citations
“…In a Japanese workplace, for example, where there is unfailing preference for collective responsibility, it is the obligation of higher-level managers to accept symbolic responsibility for the failures of their groups or group members (Morioka Todeschini, 2011). Further, although teamwork is the norm in workplaces from societies with traditionally high levels of collectivism (Jarinto, 2011), collective responsibility is not associated with all collectivistic cultures equally (Morioka Todeschini, 2011). Rather, different degrees of collective responsibility preference prevalent in different cultures may be associated more closely with the GLOBE study's (House et al, 2004) cultural value of institutional collectivism.…”
Section: Collective Responsibility Preferencementioning
confidence: 99%
“…This helps define Japanese working hours, which are exceptionally long compared to other industrialised countries (Nemoto, 2013). Jarinto (2011) found that Thai middle managers reporting to Japanese senior management were significantly less healthy due to the long hours of work than those reporting to US senior managers.…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent to which RO, RC and RA contribute to stress under different working context has not yet been studied [3]. It has been reported that MNCs’ employees have high negative stress that lead to individual physical and psychological illness which in turn results low JSF [46]. Theoretically, role stressors by its job-related antecedents lead to organizational inequity results psychological strain and diminution of employee’s performance and satisfaction.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…tress is something ordinary, unavoidable fact in anyone life, caused by many factors either at work, or with the family at home, or at the external environment (Jarinto, 2011). According to it affects both the human resources and the management at the same time.…”
Section: Introductionmentioning
confidence: 99%